Rediscovery of Mictopholis austeniana (Annandale, 1908)(Squamata: Agamidae) - Das, A.; Das, I. (The Herpetological Society of Japan, 2007)
The poorly-known agamid lizard, Mic-topholis austeniana, hitherto known from theunique holotype collected nearly a century agofrom “Hills near Harmatti” (in Arunachal Pradesh,Northeast India), is reported from two sites inArunachal Pradesh. The colouration of a livespecimen is described and the species illustratedin colour for the first time.